Is Otherness Represented in Songhay-Zarma society ? A case study of the 'Tula' story - (:unkn) unknown (My University, 2012)
This communication will examine the representations of otherness and identity in a special society: the Songhay-Zarma of Niger. I will analyze how a jasare (griot, who knows and tells the genealogies and the stories of 'noble0 families) narrates the story of Tula which describes the transformation of a young girl in a spirit. This narrative approaches the transfiguration of the closest (the beloved child of a prestigious songhay family) in a evil spirit (the image of the most radical otherness), as if they were in the other an irreducible element of proximity. We will see how this transformation process appears here as a metaphor for change of status when a girl gets married. By the time dimension involved in the narrative, this narrative allows us to deconstruct the process that lies at the heart of representations of self and others in a specific society and "dissects" the linguistic mechanism behind the representations, but also mechanisms of appropriations and exclusions. For the question of otherness inevitably refers to a query on how the speaker - in a specific situation of communication - perceives himself, we will see that the other can be built only in opposition to oneself and to the familiar. Dans cette communication, j'étudie les représentations de l'altérité et de l'identité dans une société spécifique: les Songhay-Zarma du Niger. J'y analyse comment un jasare (griot, qui connaît et raconte les généalogies et les histoires des familles dites "nobles") narre l'histoire de Toula qui décrit la transformation d'une jeune fille en génie. Ce récit aborde explicitement la transfiguration du plus proche (l'enfant chérie d'une prestigieuse famille songhay) en un génie malfaisant (image de l'altérité la plus radicale), comme s'il existait toujours dans l'autre une part irréductible de proximité. Nous verrons comment ce processus de transformation apparaît comme ici comme métaphore des changements de statut qu'une jeune fille v
Keywords: African Research